2011
DOI: 10.1179/136217110x12785889549949
|View full text |Cite
|
Sign up to set email alerts
|

High speed imaging technique Part 2 – High speed imaging of power beam welding phenomena

Abstract: The high speed imaging technique is an attractive tool to elucidate welding phenomena. In this paper, applications of this technique are reviewed in order to understand the power beam welding phenomenon. Monochromatic imaging technique, which can take pictures of plasma with any specific spectrum wavelength, is used to analyse state of the laser induced plasma and distribution of some species, such as ions and atoms of gases and metals. During electron beam welding, intermittent melting process and spiking phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 81 publications
1
18
0
Order By: Relevance
“…7 demonstrates the porosity distribution in the longitudinal section at the centerline of the weld metal with different beam offset positions. Until now, an unequivocal explanation for porosity formation in titanium welds is unavailable, most research studies indicated that keyhole instability was the main reason for porosity formation [14][15][16][17][18].…”
Section: Appearance Of the Weld Jointsmentioning
confidence: 98%
“…7 demonstrates the porosity distribution in the longitudinal section at the centerline of the weld metal with different beam offset positions. Until now, an unequivocal explanation for porosity formation in titanium welds is unavailable, most research studies indicated that keyhole instability was the main reason for porosity formation [14][15][16][17][18].…”
Section: Appearance Of the Weld Jointsmentioning
confidence: 98%
“…For vertical up and vertical down welding positions, although the dimensions and solidifying time of weld pools can be similar when laser welding with the same welding parameters, there exist totally different escape routes. For vertical up welding position ( Figure 9 a), the voids or gas bubbles formed will move upwards in the weld pool in response to the buoyancy, similarly to that revealed using a transmission X-ray imaging system in the laser welding of other materials, such as aluminum alloys and steels [ 18 , 19 ]. Some of these voids and bubbles will move out of the weld pool through the interface between the weld pool and keyhole before the metal solidifies, while others cannot move out of the weld pool and form pores in the solidified welds.…”
Section: Discussionmentioning
confidence: 71%
“…The visual detection method is the most promising seam recognition technology, due to its abundant information, non-contact with workpiece, high precision and good sensitivity [ 2 , 3 , 4 ]. However, there are serious challenges when detecting the seam of the aerospace components [ 5 , 6 , 7 ]: Specular reflection surface of the workpiece.…”
Section: Introductionmentioning
confidence: 99%